2016
DOI: 10.1038/jhh.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Family member-based supervision of patients with hypertension: a cluster randomized trial in rural China

Abstract: Empirical evidence has suggested that social support from family can help patients take their medicines correctly. This study aims to evaluate the role of a family member-based supervision package in the management of hypertension using a cluster randomized trial in rural China. We recruited patients with hypertension from four villages in Yangzhong and randomly allocated them to the control group (n=288) and the intervention group (n=266). A family member-based supervision package was applied to the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 42 publications
3
31
0
6
Order By: Relevance
“…Table provides an overview of the 48 included studies . Nine studies reported two comparisons (designated as different follow‐up duration and intervention intensity). A total of 14 568 participants from 20 provinces or regions were included.…”
Section: Resultsmentioning
confidence: 99%
“…Table provides an overview of the 48 included studies . Nine studies reported two comparisons (designated as different follow‐up duration and intervention intensity). A total of 14 568 participants from 20 provinces or regions were included.…”
Section: Resultsmentioning
confidence: 99%
“… 32 Strategies of engaging family members in hypertension management have shown promising results in rural China, must be encouraged in South Asia. 33 …”
Section: Discussionmentioning
confidence: 99%
“…The greatest prevalence worldwide for hypertension is in the African Region, where up to 46% of adults aged 25 or over in 2008 had hypertension [2], with up to three quarters or more of hypertensive patients currently failing to achieve target blood pressure (BP) goals [7−12]. It is perceived that a lack of adherence to medication is the major causative factor for uncontrolled hypertension [1,4,[6][7][8][11][12][13][14][15][16]. Non-adherence to medicines affects up to 30-50% of patients or more with chronic conditions including hypertension [8,17,18], with poor adherence levels seen even in the first year of treatment [12,19,20].…”
Section: Introductionmentioning
confidence: 99%